Design and Development of a Web-Monitored Integrated Electricity KWh Meter Using an IoT-Based Microcontroller - Khoirul Ahmat Efendi; Asni Tafrikhatin; Jati Sumarah; Juri Benedi; El Vionna Laellyn Nurul Fatich; Tegar Prasetyo (Politeknik Piksi Ganesha Indonesia, 2026)
This study aims to develop an Internet of Things (IoT)-based electrical energy (kWh) monitoring system using an ESP32 microcontroller integrated with a web monitoring platform. The system employs ACS712 current and ZMPT101B voltage sensors to measure voltage, current, power, and electrical energy in real time. The research method used is Research and Development (R&D) with the 4D model, consisting of define, design, development, and dissemination stages. The test results indicate that the ZMPT101B sensor has an error rate of 0.49%–0.81%, while the ACS712 sensor has an error rate of 4.0%–14.2%. Measurement data were successfully transmitted and displayed on the monitoring website through an internet connection. The developed system is capable of providing real-time electrical energy monitoring with adequate accuracy and easy accessibility for users.